Working Memory Reloaded: Tyrosine Repletes Updating in the N-Back Task - Colzato, Lorenza; Jongkees, Bryant; Sellaro, Roberta; Hommel, Bernhard (Frontiers in Behavioral Neuroscience, 2013)
In this study we tested the idea that the food supplement L-Tyrosine (TYR) repletes resources required for cognitive-control operations. We investigated whether the “updating” (and monitoring of) working memory (WM) representations, a key cognitive-control function, can be promoted by administering TYR, the biochemical precursor of dopamine. Participants performed an N-back task where we compared the WM-demanding 2-back condition with the WM-undemanding 1-back condition. As expected, TYR promoted performance in the more demanding (2-back) but not in the easier (1-back) condition, suggesting that TYR selectively targets cognitive-control operations. This result suggests that TYR can replete cognitive resources when more control is needed and, more generally, that food can act as a cognitive enhancer.